Experimental gillnet study to inform future large fish monitoring in the San Francisco Estuary - Dylan Keating Stompe; James A. Hobbs (California Fish and Wildlife Journal)
Fishery independent monitoring in the San Francisco Estuary (SFE) includes extensive coverage by the many trawl- and seine-based surveys of the Interagency Ecological Program (IEP). These surveys primarily sample small forage fishes and/or juvenile life stages of larger fishes due to the relatively small net dimensions, mesh sizes, and tow speeds. As a result, the adult life stage of many SFE fish species is not completely sampled, representing a shortcoming in our ability to track changes in age-structured regional fish assemblages. To help fill this monitoring gap, we conducted an experimental gillnetting effort in the spring of 2023. We employed American Fisheries Society experimental gillnets in a stratified random sampling design in the North Delta, California, USA. In total, we caught 16 fish species during 141 approximately one-hour gillnet sets, including 33 paired day and night sets to test diurnal effects on catch. On average, fishes caught in this study were substantially larger than those caught by trawl- and seine-based surveys. Ordination analyses revealed a high degree of overlap in sampled fish assemblages between the three North Delta subregions (Cache Slough Complex, Lindsey Slough Complex, Liberty Slough Complex), with significant differences detected for only the Lindsey Slough Complex. When testing diel effects on catch, significant differences in species assemblage were seen between day and night sets. However, differences in catch may not justify the added risk and complexities of night sampling except for targeted studies of benthic predators (catfishes). Finally, while over 3,000 PIT tags were deployed (primarily in Striped Bass) between this and another nearby study, only 6 PIT tags were recovered, demonstrating that greater effort or different methodologies would be required to generate mark-recapture abundance estimates in this open and highly dynamic system. This study demonstrates the efficacy of experimental gillnets in sampling the large fish community within portions of the SFE and may inform future SFE large fish monitoring.